Digital Transformation of AI in Business Communication - Achmad Yusuf Adzzu Hary; Fenesia Evelin; Fiora Therinne Gloria; Risnawati Eka Deuyanti; Mada Aditia Wardhana (Shofanah Media Berkah, 2026)
This study examines the role of Artificial Intelligence (AI) in the digital transformation of business communication through a systematic literature review method. The review aims to identify the key mechanisms and impacts of AI on communication efficiency and information quality, while also analyzing the sociocultural challenges and ethical implications of its adoption. The findings indicate that AI serves as a primary driver in enhancing transparency, reducing information asymmetry, and facilitating closer collaboration among stakeholders through digital platforms, as observed in the financial and professional services sectors. On the other hand, the implementation of AI faces challenges such as organizational cultural resistance, gaps in digital competencies, and risks related to data privacy and security. To address these barriers, the review recommends managerial strategies that emphasize transformational leadership, the development of a culture of experimentation and learning, increased cross-functional collaboration, and a human-centric approach to technology integration. The results of this study provide insights for organizations in designing and implementing AI-based digital transformation in a more effective and responsible manner.